Effectiveness of Failure Mode and Effects Analysis in managing skin complications in ICU psychiatric patients: a real-world study - Zhang, Ping; Zhu, Haiyan; Qian, Yuanyuan; Chen, Minmin; Liu, Lin (Frontiers in Psychiatry, 2025)
ObjectivePsychiatric patients are particularly vulnerable to skin injuries, which can result in severe systemic complications and higher mortality rates. Therefore, improving skin wound management for ICU psychiatric patients through Failure Mode and Effects Analysis (FMEA) is crucial. This study aims to evaluate the effectiveness of FMEA in enhancing skin wound management in ICU settings, with a focus on identifying key risk factors and implementing targeted interventions to mitigate skin complications.MethodsA real-world study was conducted in the ICU of the Fourth People’s Hospital of Nantong, China, involving 615 psychiatric patients admitted between October 2022 and October 2024. Patients were divided into two groups: the control group received traditional wound care, while the observation group was managed using FMEA-based strategies. Key risk factors were evaluated through FMEA to prioritize interventions, Logistic regression analysis was used to assess the relationship between various risk factors and skin complications, helping to identify significant predictors of adverse skin events.ResultsFMEA implementation led to a significant reduction in skin complications from 7.56% to 3.59% (χ2 = 4.69, p = 0.03). FMEA analysis identified key risk factors, including positioning management, skin hygiene, and nutritional support, with corresponding Risk Priority Numbers (RPN) calculated for each factor. Logistic regression analysis revealed that FMEA implementation was significantly associated with a reduced risk of skin complications (coefficients = -1.44, p = 0.01). Additionally, factors such as ADL, hypoalbuminemia, diabetes, and ICU length of stay were found to significantly influence the risk of skin complications (p < 0.01).ConclusionFMEA is an effective tool for enhancing skin management practices and reducing skin complications in psychiatric ICU patients. Early identification of risk factors and the implementation of personalized skin care protocols can significantly improve patient outcomes and safety.